Elizabeth Blackwell : with profiles of Elizabeth Garrett Anderson and Susan La Flesche Picotte - Klobuchar, Lisa.; World Book, Inc. (Chicago : World Book, 2007)
"A biography of Elizabeth Blackwell, the first woman to obtain an M.D. degree in the United States, with profiles of two prominent individuals, who are associated through the influences they had on one another, the successes they achieved, or the goals they worked toward. Includes recommended readings and web sites"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Blackwell, Elizabeth, -- 1821-1910.; Anderson, Elizabeth Garrett, -- 1836-1917.; Picotte, Susan LaFlesche, -- 1865-1915.; Women physicians -- United States -- Biography -- Juvenile literature